Editorial for the Special Issue of Comparative Economic Studies: 50 Years After the End of Bretton Woods—The Experiences of Small Open Economies - Alexander Rathke; Tobias Straumann; Jan-Egbert Sturm (Comparative Economic Studies, 2024)
This special issue of Comparative Economic Studies, commemorating fifty years since the end of the Bretton Woods system, examines the adjustment of small open economies to floating exchange rates and new monetary policy frameworks. Based on a workshop held at the KOF Swiss Economic Institute in June 2023, six papers analyse dimensions such as the evolution of monetary policy regimes, the impact of economic crises and the use of unconventional monetary policies in Canada, Israel, Norway, Sweden and Switzerland. The findings highlight the benefits and limitations of inflation targeting, the challenges of global financial integration and the strategic responses of central banks to maintain stability and independence, providing policymakers with valuable insights into the complex dynamics of monetary policy in the post-Bretton Woods era.
Keywords: E42; E52; E58; F31; F33; 330; Bretton Woods; Central banks; Exchange rate regimes; Inflation targeting; Monetary policy